Postmenopausal Deep Infiltrating Endometriosis of the Colon: Rare Location and Novel Medical Therapy - Benjamin M. Snyder; Joseph W. Beets; Bruce A. Lessey; Samuel R. W. Horton; Gary A. Abrams (Case Reports in Gastrointestinal Medicine)
We report an uncommon case of deep infiltrating endometriosis of the colon presenting as iron deficiency anemia nine years after hysterectomy with bilateral salpingo-oophorectomy. The endometrial implant was found at the hepatic flexure, an exceedingly rare location for endometriosis invasion with no cases distinctly reported in the literature. Additionally, the presentation of gastrointestinal endometriosis as iron deficiency anemia is not well documented in the literature. Instead of surgery, we prescribed a novel medical therapeutic approach using conjugated estrogen-bazedoxifene to antagonize the proliferative effects of estrogen on endometrial tissue. After five months of therapy and repeat colonoscopy, no evidence of endometrial tissue remained in the hepatic flexure.